Effect or different concentrations of acidic olive leaves extractmouth rinse on plaque, gingivitis and periodontal pockets onadults - K. Younis, Shaymaa; D. Salman, Faraed (Tikrit Journal of Pharmaceutical Sciences, 2023)
Aims: The aims of this study were to evaluate the effectiveness of olive leaves extract mouthrinse on the development of plaque, gingivitis, periodontal pockets in different concentrations as pure extract 50%, apple cider vinegar (ACV) extract rinse 50%, ACV + olive leave extract (OLE) 15% in acidic medium, 20% ACV + OLE mouthrinse compared with the ideal standard control mouthrinse chlorhexidine (CHX) 0.2%. Fifty adult volunteers participated in this controlled single blind cross— over study, 10 subjects for each group, one control and four experimental groups with different concentrations of the rinse for | minute twice daily during 8 weeks period, 2 weeks interval between each visit for motivation and reinforcement of application of the material. Three applied indices (plaque and gingival indices by Loe and Silness), CPITN index by Ainamo recorded at baseline, after each experimental period and at the last visit, then examining the biological activity of the material in the laboratory. It had been found that materials were effective on the three applied indices with significant percentage reduction (for OLE 50%, ACV 50%) at p < 0.001 using unpaired Z-test, and at p < 0.001, p < 0.0! for OLE + ACV 51%, OLE + ACV 20% respectively using unpaired Z-test except for some visits for the two materials. Percentage reductions for the four applied concentrations were greatest for OLE + ACV 20%, OLE ACV 15%, ACV, OLE respectively for the three applied indices with significant differences at p < 0.05 using repeated measures analysis of variance and Duncan test. Using OLE mouthrinse in different acidic concentrations offer benefit in plaque. gingival, periodontal pocket depth reductions, but it is much lower than that of CHX 0.2% mouthrinsc.